2019
DOI: 10.3892/ijmm.2019.4410
|View full text |Cite
|
Sign up to set email alerts
|

The aqueous extract of Gentianella acuta improves isoproterenol‑induced myocardial fibrosis via inhibition of the TGF‑β1/Smads signaling pathway

Abstract: Gentianella acuta (G. acuta) is one of the most commonly used herbs in Chinese Mongolian medicine for the treatment of heart disease. Previously, it was found that G. acuta ameliorated cardiac function and inhibited isoproterenol (ISO)-induced myocardial fibrosis in rats. In this study, the underlying anti-fibrotic mechanism of G. acuta was further elucidated. Histopathological changes in the heart were observed by hematoxylineosin, Masson trichrome and wheat germ agglutinin staining. Relevant molecular events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
10
2
Order By: Relevance
“…Myofibroblasts can express a contractile protein such as α-SMA and produce excessive collagen during fibrosis progression (Weber and Diez, 2016;Song et al, 2020). Our previous studies demonstrated that TGF-β1 expression was upregulated in fibrotic heart tissue, and G. acuta downregulated the upregulation and ameliorated myocardial fibrosis by inhibiting TGF-β1 signaling Yang et al, 2020). This work evaluated the effect of BEL, a vital component of G. acuta, on cell viability with or without TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myofibroblasts can express a contractile protein such as α-SMA and produce excessive collagen during fibrosis progression (Weber and Diez, 2016;Song et al, 2020). Our previous studies demonstrated that TGF-β1 expression was upregulated in fibrotic heart tissue, and G. acuta downregulated the upregulation and ameliorated myocardial fibrosis by inhibiting TGF-β1 signaling Yang et al, 2020). This work evaluated the effect of BEL, a vital component of G. acuta, on cell viability with or without TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…In these regions, Ewenki people keep a habit of drinking "guixincao" tea, and employ it to treat angina by water decoction or chewing for a long time (Wunir et al, 2009;Li et al, 2010). Our previous studies demonstrated that TGF-β1 was elevated in isoprenaline (ISO)induced cardiac fibrotic tissue, and G. acuta ameliorated myocardial fibrosis by inhibiting TGF-β1/Smads signaling Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Inner Mongolia, G. acuta has been applied to treat angina by the local herdsmen, and increasing studies have reported that it can protect the heart from injury [ 20 ]. We have verified that G. acuta and its xanthone compound BEL could alleviate myocardial fibrosis by preventing TGF- β 1 signalling [ 19 , 21 ]. The present study further illuminated the mechanism of BEL on myocardial fibrosis in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages, Lys311 is a key succinylated site in the regulation of PKM2 activity, promoting inflammation (Wang et al, 2017 ). O-GlcNAcylation plays an important role in the regulation of cellular signaling, translation, and transcription in response to nutrients and stresses (Li et al, 2019 ; Ong et al, 2018 ); glycosylation is important in the correct folding and trafficking of proteins, such as Relmα, CD206, and CD301, which are destined for secretion or exportation to the cell surface in anti-inflammatory macrophages (Jha et al, 2015 ).…”
Section: Metabolite–macromolecules Interactions and Modificationsmentioning
confidence: 99%